Applied and involved social sciences from the university: The AFRICAInEs team – research and studies applied to development (SEJ-491) - Vieitez Cerdeño, Soledad; Manzanera Ruiz, Roser (Revista Española de Desarrollo y Cooperación, 2024)
In this article we analyse the applied and involved trajectory of the Andalusian research team of the University of Granada: AFRICAInEs (SEJ-491), from 2006 to the present, whose clear objective and commitment is and has been social transformation, beyond merely contributing to the “science” in itself, with a gender perspective and culturally compatible perceptions of development, through the incorporation of academic and research content and practices that address the structural and most deep-rooted aspects of inequality and incorporate the epistemologies of the south, feminisms or anti-racisms in an intersectional fashion.